Integration of Islamic Socio-Cultural Values in Nature-Based Education: A Systematic Literature Review Study of Nature Schools and Eco-Pesantren (Indonesia) With Forest Schools (Europe) - Nurkamaliyah, Afnie Rizky; Mahmud; Erihadiana, Mohamad; Nazar, Reza Fauzi; Halimah, Nenden Ahadiah; Nirwati (Global Writing Academica Researching & Publishing, 2025)
This study examines the integration of Islamic socio-cultural values within nature-based environmental education by comparing three educational models: Sekolah Alam and eco-pesantren in Indonesia, and Forest Schools in Europe. The growing global ecological crisis highlights the need for educational approaches that promote not only cognitive development but also value internalization, character formation, and ecological consciousness. Using a qualitative design with a Systematic Literature Review (SLR) guided by PRISMA 2020, this study reviewed literature from Scopus, Web of Science, DOAJ, Google Scholar, GARUDA, and ResearchGate published between 2019 and 2025. Of the 1,546 initial records, 30 studies met the inclusion criteria and were synthesized thematically. The findings show that: (1) Sekolah Alam cultivates ecological character through experiential learning grounded in Islamic values and local wisdom; (2) Eco-pesantren integrate Islamic ecological theology, khalifah (stewardship), amanah (trust), ihsan (excellence), and ecological monotheism, into conservation practices, organic farming, and waste management; (3) Forest Schools emphasize exploration, learner agency, and wellbeing without religious foundations; and (4) all three models foster emotional and ethical connections to nature while differing in value orientations. The proposed Islamic Socio-Cultural and Nature-Based Environmental Education Model offers a framework for developing faith-based and sustainability-oriented Islamic education curricula.